Factors Influence on Debt Maturity Structure (In Manufacturing Companies Registered on the IDX for the 2019 - 2021 Period) - Feryanto Surbakti; P. Basuki Hadiprajitno (Journal of Business Social and Technology, 2024)
This study examines the effectProfit Management, Company Size, Asset Maturity, Leverage on Debt Maturity Structure(Manufacturing Companies Registered on the IDX for the 2019 - 2021 period). The research population is pThe population for this research is all publicly listed companies on the IDX for the 2019-2021 period. The samples were taken based on purposive sampling, which means the criteria used are as follows: (a) Manufacturing companies listed on the IDX for 2019-2021, (b) Financial reports are accessible, (c) The required variable data is available.Furthermore, to perform data analysis, multiple linear regression through the use of SPSS software as a tool is used in this study. The research results show that hhypothesis 1 earnings management (DA) has a sig value of 0.027<0.05 and Î²1 -0.170<0 then H1 is accepted, meaning that earnings management has a negative effect on the structure of debt maturity. Hypothesis 2 firm size (SIZE) has a sig value of 0.000<0.05 and Î²2 0.018>0, so H2 is accepted, meaning that firm size has a positive influence on the structure of debt maturity. Hypothesis 3: asset maturity (ASMAT) has a sig value of 0.000<0.05 and Î²3 0.528>0, so H3 is accepted, meaning that asset maturity has a positive influence on the debt maturity structure. Hypothesis 4 leverage (DAR) has a sig value of 0.510> 0.05, so H4 is rejected, meaning that leverage has no effect on the structure of debt maturity.